Prioritisation mechanisms to support incremental development of agent systems. (14th December 2007) - Padgham, Lin; Perepletchikov, Mikhail
It is often necessary to partition a project into different priority levels and to develop incrementally. This paper presents a mechanism whereby a developer can prioritise scenarios on a five point scale, leading to automated, coherent partitioning of all required design entities, according to the three IEEE defined priority levels of essential, conditional and optional, which are used in many companies. This allows for automated support to guide the developer as to what design artefacts need to be developed at each phase. The developer can indicate the relative sizes desired for the three partitions and the algorithm described will attempt to get as close to this as possible. It is also possible to move items manually to achieve better sized partitions, as long as priority orderings are not violated. The approach is fast and easy to apply at various times during development, as needed.